Women's intentions to breastfeed: a population‐based cohort study. Issue 12 (17th July 2013) - Lutsiv, O; Pullenayegum, E; Foster, G; Vera, C; Giglia, L; Chapman, B; Fusch, C; McDonald, SD
<x xml:space="preserve">Abstract</x> Objective Given that intention to breastfeed is a strong predictor of breastfeeding initiation and duration, the objectives of this study were to estimate the population‐based prevalence and the factors associated with the intention to breastfeed. Design Retrospective population‐based cohort study. Setting All hospitals in Ontario, Canada (1 April 2009–31 March 2010). Population Women who gave birth to live, term, singletons/twins. Methods Patient, healthcare provider, and hospital factors that may be associated with intention to breastfeed were analysed using univariable and multivariable regression. Main outcome measures Population‐based prevalence of intention to breastfeed and its associated factors. Results The study included 92 364 women, of whom 78 806 (85.3%) intended to breastfeed. The odds of intending to breastfeed were higher amongst older women with no health problems and women who were cared for exclusively by midwives (adjusted OR 3.64, 95% CI 3.13–4.23). Being pregnant with twins (adjusted OR 0.73, 95% CI 0.57–0.94), not attending antenatal classes (adjusted OR 0.58, 95% CI 0.54–0.62), having previous term or preterm births (adjusted OR 0.79, 95% CI 0.78–0.81, and adjusted OR 0.87, 95% CI 0.82–0.93, respectively), and delivering in a level–1 hospital (adjusted OR 0.85, 95% CI 0.77–0.93) were associated with a lower intention to breastfeed. Conclusions In this population‐based study ~85% of women intended to breastfeed their babies. Key factors that are associated with the intention to breastfeed were identified, which can now be targeted for intervention programmes aimed at increasing the prevalence of breastfeeding and improving overall child and maternal health.